2018
DOI: 10.1051/0004-6361/201731834
|View full text |Cite
|
Sign up to set email alerts
|

Sloshing in its cD halo: MUSE kinematics of the central galaxy NGC 3311 in the Hydra I cluster

Abstract: Context. Early-type galaxies (ETGs) show a strong size evolution with redshift. This evolution is explained by fast "in-situ" star formation at high-z followed by a late mass assembly mostly driven by minor mergers that deposit stars primarily in the outer halo. Aims. We aim to identify the main structural components of the Hydra I cD galaxy NGC 3311 to investigate the connection between the central galaxy and the surrounding stellar halo. Methods. We produce maps of the line-of-sight velocity distribution (LO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 118 publications
8
48
0
1
Order By: Relevance
“…While this effect would have little impact on the decomposed spectra if the halo stellar populations are uniform throughout, the presence of substructures within the halo due to accreted material would affect the spectra. Fits to imaging data by Arnaboldi et al (2012) and Barbosa et al (2018) have revealed three distinct substructures within the field-of-view of the MUSE data, which are attributed to tidal tails. As a result, if the stellar populations of these substructures are significantly different to that of the halo, it is likely that the decomposed halo spectrum obtained from this data will be biased towards these properties.…”
Section: Analysis Of the Fit Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…While this effect would have little impact on the decomposed spectra if the halo stellar populations are uniform throughout, the presence of substructures within the halo due to accreted material would affect the spectra. Fits to imaging data by Arnaboldi et al (2012) and Barbosa et al (2018) have revealed three distinct substructures within the field-of-view of the MUSE data, which are attributed to tidal tails. As a result, if the stellar populations of these substructures are significantly different to that of the halo, it is likely that the decomposed halo spectrum obtained from this data will be biased towards these properties.…”
Section: Analysis Of the Fit Parametersmentioning
confidence: 97%
“…It must be noted at this point that the models we use for NGC 3311 in this study assume that the halo is smooth and symmetric both inside and outside of the available field of view. In reality however, Arnaboldi et al (2012) and Barbosa et al (2018) found that the halo is asymmetric, with an excess of light towards the north east of the central galaxy due to the halo lying off-centre and the presence of what that they identified as a tidal stream from an in falling galaxy. This effect can be seen in Fig.…”
Section: Analysis Of the Fit Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…A different approach is to consider stellar velocities. It is motivated by the rising radial velocity dispersion profiles that approach the cluster dispersion, i.e., the relative velocities of the cluster galaxies (Ventimiglia et al 2010;Toledo et al 2011;Arnaboldi et al 2012;Melnick et al 2012;Murphy et al 2014;Bender et al 2015; Barbosa et al 2018). The ICL is hereby the dynamically hot component that is kinematically controlled by the gravitational potential of the whole cluster, i.e., unbound from the BCG.…”
Section: Introductionmentioning
confidence: 99%
“…One of the nearest cD-galaxies is NGC 3311, the central galaxy in the Hydra I galaxy cluster. Recent publications on NGC 3311 are mainly from our group (Ventimiglia et al 2008(Ventimiglia et al , 2010(Ventimiglia et al , 2011Coccato et al 2011;Misgeld et al 2011;Richtler et al 2011;Arnaboldi et al 2012; Barbosa et al 2016Barbosa et al , 2018. Photometric and kinematical studies using the galaxy light, planetary nebulae (PNe) and globular clusters (GCs) clearly demonstrate the close connection of the inner galaxy with its host cluster.…”
Section: Introductionmentioning
confidence: 99%